Acetyl cholinesterase: a potential target for Alzheimer’s disease intervention (Journal of Patan Academy of Health Sciences, 2020)
Alzheimer's disease is a neurological disorder in which the death of brain cells causes memory loss and cognitive decline. The role of treatment is not limited to pharmacology, but also involves many factors, such as the psychological, social, and economic aspects of the patient and family. It is important to consider the use of AChe inhibitors in patients with mild to moderate AD, despite cost issues and in the absence of any other immediate progression. Although there are allots of currently available inhibitor for acetyl cholinesterase but there is no selective potent inhibitor for AD. so, there is an urgent need discover of compounds that are active against Acetyl cholinesterase, along  with there is need of molecular modeling for  identifying functional groups that may be important for inhibiting Acetyl cholinesterase activity.